PENETAPAN KADAR FENOLIK TOTAL DAN FLAVONOID TOTAL EKSTRAK BERAS HITAM (Oryza sativa L) DARI KALIMANTAN SELATAN - Anna Khumaira Sari; Noverda Ayuchecaria (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
The black rice contains anthocyanin compounds which are included in the flavonoids and phenolic compounds. Flavonoids contained in black rice are phenolic components that act as a preventive of hydroxyl and superoxide radicals by protecting membrane lipids against damaging oxidation reactions and phenol compounds also have bacteriocid, antimetic, antihelmintic, antiinflammatory, antimicrobial, anticancer and other degenerative diseases. The aim of this research were to measure total phenolic content and total flavonoid in ethanol extract of black rice (Oryza sativa L). Total phenol content were measured by Folin-Ciocalteu method with gallic acid mean while total flavonoid content were measured by colorimetry method using reagent AlCl3 10% and 5% acetic acid. There are seven variation samples of black rice obtained from seven different places in South Kalimantan. The result of this study, qualitative analysis showed that all samples positive contained flavonoids, alkaloids and tannins. The total phenol content of the seven samples was 100,58 ± 1,344; 91.14 ± 1.699; 96.50 ± 1.529; 77.64 ± 0.462; 81,16 ± 0,614; 112.47 ± 1.040; 81,50 ± 2,928 mgGAE/mg extract and the percent of total flavonoid content from seven samples was 8,53 ± 0,208%; 8.11 ± 0.343%; 7.69 ± 0.446%; 6.03 ± 0.227%; 4.97 ± 0.169%; 3.74 ± 0.210%; 5.02 ± 0.403%.